PENGEMBANGAN MEDIA PEMBELAJARAN BERBASIS WEB PADA MATERI TOPOLOGI DAN ARSITEKTUR JARINGAN DENGAN APLIKASI CANVA DI KELAS XI TKJ 1 SMK SORE TULUNGAGUNG - Sofyan Aji Lukmana; Abdul Haris Indra Kusuma (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study was motivated by the limited use of learning media in the Network Infrastructure Administration subject for Class XI TKJ 1 at SMK SORE Tulungagung. Microsoft PowerPoint was still the primary instructional medium, resulting in a less engaging learning experience. Students also experienced difficulties in understanding the topics of Network Topology and Network Architecture and often forgot previously learned material. This study aimed to develop a web-based learning media using Canva for these topics and to evaluate its feasibility. The research employed the Research and Development (R&D) method using the ADDIE model, which consists of the Analyze, Design, Development, Implementation, and Evaluation stages. The participants included one media expert, one material expert, nine students in the small-group trial, and thirty students in the large-group trial. Data were collected through observations, interviews, and questionnaires and analyzed descriptively using percentage-based feasibility analysis. The results showed that the developed learning media achieved a feasibility score of 100% from the media expert, 98.18% from the material expert, 91.45% from the small-group trial, and 93.69% from the large-group trial, all categorized as Very Feasible. The overall average feasibility score was 95.83%, indicating that the web-based learning media developed using Canva is highly feasible for classroom implementation. Therefore, the developed media can serve as an effective, interactive, and engaging learning resource to support the teaching and learning process in the Network Infrastructure Administration subject for Class XI TKJ 1 students at SMK SORE Tulungagung.